Pharmacogenomics of lung cancer: with a view to address EGFR-targeted therapies. (September 2007) - Joshi, Victoria A; Kucherlapati, Raju
Epidermal growth factor receptor (EGFR)-targeted therapies have demonstrated variable success in treating individuals with non-small-cell lung cancer. Understanding the molecular mechanisms of response and resistance to this class of treatment has led to patient selection strategies that may improve outcomes. The second generation of EGFR-targeted therapies is now under clinical evaluation and may prove to be successful at circumventing a portion of primary or acquired resistance to first-generation tyrosine kinase inhibitors. These principles are generally applicable to the field of targeted therapy and predictive pharmacogenomics.